THE EFFECT OF ULTRAVIOLET RADIATION ON SEROTONIN LEVELS: A META-ANALYSIS - Жванський, Тимур; Кушнір, Олександра (SWorldJournal, 2025)
Relevant studies have demonstrated a link between depression and ultraviolet B, but a direct link between them has yet to be investigated.Objective: To analyze the available studies on the effect of ultraviolet radiation on serotonin levels in the human